A novel variant in LPL gene is associated with familial combined hyperlipidemia. (10th October 2019) - Taghizadeh, Eskandar; Ghayour‐Mobarhan, Majid; Ferns, Gordon A.; Pasdar, Alireza
Abstract: Familial combined hyperlipidemia (FCHL) is a common genetic disorder characterized by increased fasted serum cholesterol, triglycerides, and apolipoprotein B‐100. Molecular genetic techniques such as next generation sequencing have been very successful methods for rare variants finding with a moderate‐to large effect. In this study, we characterized a large pedigree from MASHAD study in northeast Iran with coinheritance of FCHL and early‐onset coronary heart disease. In this family, we used whole‐exome sequencing and Sanger sequencing to determine the disease‐associated gene. We identified a novel variant in the LPL gene, leading to a substitution of an asparagine for aspartic acid at position 151. The D151N substitution cosegregated with these characters in all affected family members in the pedigree but it was absent in all unaffected members in this family. We speculated that the mutation D151N in LPL gene might be associated with FCHL and early‐onset coronary heart disease in this family. However, the substantial mechanism requires further investigation.